2017
DOI: 10.1002/brb3.691
|View full text |Cite
|
Sign up to set email alerts
|

Male‐to‐female gender dysphoria: Gender‐specific differences in resting‐state networks

Abstract: IntroductionRecent research found gender‐related differences in resting‐state functional connectivity (rs‐FC) measured by functional magnetic resonance imaging (fMRI). To the best of our knowledge, there are no studies examining the differences in rs‐FC between men, women, and individuals who report a discrepancy between their anatomical sex and their gender identity, i.e. gender dysphoria (GD).MethodsTo address this important issue, we present the first fMRI study systematically investigating the differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
(82 reference statements)
0
16
0
Order By: Relevance
“…With regard to the third metric used in the present study, the rs-fMRI, the data are sparse. Ute Habel's group, however, investigated several different networks in a TrW population of mixed sexual orientation, and found that "untreated" TrW had a "weaker" functional connectivity not only in the inferior temporal lobe in relation to male (presumably heterosexual) controls but also in the right calcarine gyrus and the left dorsolateral prefrontal cortex in relation to TrW who had received cross-sex hormonal treatment (Clemens et al 2017). These data concur with the present findings of weaker functional connectivity among TrW and TrM.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the third metric used in the present study, the rs-fMRI, the data are sparse. Ute Habel's group, however, investigated several different networks in a TrW population of mixed sexual orientation, and found that "untreated" TrW had a "weaker" functional connectivity not only in the inferior temporal lobe in relation to male (presumably heterosexual) controls but also in the right calcarine gyrus and the left dorsolateral prefrontal cortex in relation to TrW who had received cross-sex hormonal treatment (Clemens et al 2017). These data concur with the present findings of weaker functional connectivity among TrW and TrM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition. differences in resting-state brain networks in transgender women compared to cisgender ones have been reported [ 21 , 22 ]. Moreover, combining both resting-state functional connectivity and behavioral data, gender identity in transgender and in cisgender persons has been recently examined, showing that machine learning algorithms could predict distinct brain connectivity patterns in cis and trans people [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of sex differences in the synchronization in our study was consistent with previous findings of sex differences in other psychiatric diagnosis. [73][74][75][76] The synchronization differences found between both sexes could indicate that male offenders have some type of functional impairment associated with cortical connections involved in decision making and emotional regulation different from females.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of sex differences in the synchronization in our study was consistent with previous findings of sex differences in other psychiatric diagnosis. 73-76…”
Section: Discussionmentioning
confidence: 99%